INTERDISCIPLINARY CONNECTIONS IN TEACHING HISTORY - Bakhronov Bekhruz Buri ugli (Journal Park Publishing, 2025)
This article is devoted to the study of interdisciplinary connections in teaching history. The work analyzes the theoretical foundations of interdisciplinary education, explaining its essence, principles, and pedagogical significance. It emphasizes the role of history as an integrative subject that connects different branches of human knowledge such as geography, literature, economics, and culture. The results of the study confirm that interdisciplinary teaching is one of the most effective strategies for improving the quality of history education and developing students’ intellectual and creative potential.
Keywords: History teaching, interdisciplinary connections, education, integration, pedagogy, project-based learning, collaboration, motivation, innovation.